Computed tomography and magnetic resonance colonography - Vegar-Zubović, Sandra (Radiology and oncology (Ljubljana), 2007)
Background. Colon cancer is the second leading cause of cancer death in the western world. Adenomatous colorectal polyps, which are found in 30-50% of Americans more than 50 years old, are recognized as important precursors of malignancy. Probably most of the invasive colon carcinomas arise from polyps. For this reason an early detection of these polyps and their complete removal is a recognized strategy for the prevention of colon cancer. So far no single method for an early diagnosis of colon polyps or colon cancer offers high sensitivity and specificity along with law cost and good patient acceptance. Endoscopic colonoscopy allows the accurate detection of very small lesions andhas since almost completely replaced fluoroscopy. Cross-sectional imaging techniques, including magnetic resonance imaging (MRI) and compuied tomography(CT), are increasingly being considered imaging modalities for the detection of colorectal polyps. Conclusions. CT and MR colonography are new techniques for imaging of the colon. In symptomatic pafients, these new techniques show promising results for the detection of polyps equal to or larger than 1 cm in diameter.
Keywords: Colonic Neoplasms; Colonoscopy; debelo črevo; Debelo črevo, novotvorbe; Diagnosis; diagnostika; jedrska magnetna resonanca; kolonografija; Kolonoskopija; Magnetic Resonance Imaging; Magnetna resonanca slikovna; Meta-analiza; Meta-Analysis; novotvorbe; rak (medicina); Tomografija radiografska, računalniška; Tomography, X-Ray Computed; tumor